A Analisa Implementasi Pembelajaran Daring di Sekolah Tingkat Dasar Se-Kota Serang - Najat, Syifaun; Hilmiyati, Fitri; Farhurohman, Oman (Educational Consultant & Counseling Career (EC3) Mataram, 2023)
Pandemic Covid-19 is a phenomenon that has a very important impact on the order of life. Education is one of the fields that has felt the impact of the pandemicCovid-19 in Indonesia. Based on a circular relating to policies for implementing education during the emergency deployment period Covid-19 which has the impact of changing normal learning activities to distance learning. A program that is unusual to implement is certainly a program that needs to be analyzed regarding the implementation of the program. Primary level schools in Serang City are one of the objects that need to be explored regarding the implementation of distance learning. The aim of this research is to find out how online learning was implemented during the pandemic Covid-19 in elementary schools throughout the city of Serang. The method used is an evaluative qualitative research method using an evaluation model responsive evaluative according to Robert Stake's. Data collection techniques used include interviews, observation and documentation. The research results show that the implementation of online learning during the pandemic Covid-19 in elementary schools throughout the city of Serang is said to be quite conducive. This is of course adjusted to the conditions of each school. Facts on the ground show that the implementation of online learning is also influenced by internal and external factors.